The effect of joint surface contours and glass fiber reinforcement on the transverse strength of repaired acrylic resin: An in vitro study - Nayana Anasane; Yogesh Ahirrao; Deepa Chitnis; Suresh Meshram (Wolters Kluwer Medknow Publications, 2013)
Background : Denture fracture is an unresolved problem in complete denture prosthodontics. However, the repaired denture often experiences a refracture at the repaired site due to poor transverse strength. Hence, this study was conducted to evaluate the effect of joint surface contours and glass fiber reinforcement on the transverse strength of repaired acrylic resins. Materials and Methods: A total of 135 specimens of heat polymerized polymethyl methacrylate resin of dimensions 64 × 10 × 2.5 mm were fabricated. Fifteen intact specimens served as the control and 120 test specimens were divided into four groups (30 specimens each), depending upon the joint surface contour (butt, bevel, rabbet and round), with two subgroups based on type of the repair. Half of the specimens were repaired with plain repair resin and the other half with glass fibers reinforced repair resin. Transverse strength of the specimens was determined using three-point bending test. The results were analyzed using one-way ANOVA and Tukey post-hoc test (α= 0.05). Results: Transverse strength values for all repaired groups were significantly lower than those for the control group ( P < 0.001) (88.77 MPa), with exception of round surface design repaired with glass fiber reinforced repair resin (89.92 MPa) which was significantly superior to the other joint surface contours ( P < 0.001). Glass fiber reinforced resin significantly improved the repaired denture base resins as compared to the plain repair resin ( P < 0.001). Conclusion: Specimens repaired with glass fiber reinforced resin and round surface design exhibited highest transverse strength; hence, it can be advocated for repair of denture base resins.